Determinants of cardiovascular and all-cause mortality in northwest Russia : a 10-year follow-up study - Sidorenkov, Oleg; Nilssen, Odd-Ragnar; Grjibovski, Andrej (Annals of Epidemiology, 2012)
This article is part of Oleg Sidorenkov's doctoral thesis available in Munin at http://hdl.handle.net/10037/3589 Abstract PURPOSE: To study conventional and novel risk factors associated with high cardiovascular disease (CVD) and all-cause mortality in Russia. METHODS: A prospective cohort study of 3704 adults was performed in Arkhangelsk. The baseline examination was conducted in 1999-2000. The average follow-up was 10.2 years. Information on lifestyle and marital, educational, and psychosocial status was self-reported in a questionnaire. Data on risk factors were collected in a medical examination that included the drawing of blood samples. RESULTS: By October 2010 a total of 147 male and 95 female deaths had occurred. In 59 male and 20 female deaths in which a diagnosis was made by a forensic pathologist, the autopsy data were studied to extract information on post-mortem blood alcohol concentration. A positive blood alcohol concentration was found in 21 (36%) male and 6 (30%) female forensic autopsies. Women reporting consumption of at least 80 g of alcohol monthly and consumption of 5 or more alcohol units during one drinking episode had a greater risk of cardiovascular death than abstainers; relative risk (RR) was 5.06 (95% confidence interval [95% CI], 1.54-16.7) and 3.21 (95% CI, 1.07-9.58), respectively. ApoB/ApoA1-ratio was the strongest predictor of CVD and all-cause death in men (RR, 7.62; 95% CI, 3.15-18.4; and RR, 4.39; 95% CI, 2.22-8.68, respectively) and CVD death in women (RR 3.12; 95% CI, 1.08-8.98). Men who were obese and had obtained a university education had a 40% lower risk of all-cause death. Low serum albumin was associated with high mortality in both genders. CONCLUSIONS: Hazardous alcohol consumption is an independent risk factor of CVD mortality in women. The mechanisms behind its damaging effect are not yet clear. Nutritional factors such as serum albumin are important predictors of all-cause mortality in both genders.